Butterflies - Vane - Wright, Dick (London Natural History Museum, 2003)
Looking at one of the most popular of the insect groups, Dick Vane-Wright explores what it means to be a butterfly by looking at the biology and diversity of the major group of day-flying Lepidoptera. The text aims to be an absorbing addition to the bookshelves of both the amateur and professional.
Include Colors Illustration,Glossary and Index
Keywords: Butterflies